Characterization of the Kinematic Evolution of the Hongshiyan Landslide Using the Material Point Method - Yang, Yue; Wang, Rubin; Xu, Weiya; Wang, Yunzi; Yan, Long (Frontiers in Physics, 2022)
In 2014, a landslide disaster occurred at Hongshiyan in Ludian County, Yunnan Province, China, causing the landslide-dames in Niulanjiang River. Scholars have studied the characteristics and causal mechanisms of this landslide and obtained substantial results. However, the kinematic evolution characteristics of the landslide remain relatively unclear. To resolve this problem, we introduced the Material Point Method (MPM) to study large-scale deformations for simulation analysis. The results showed that the movement of the slide body could be divided into three stages: accelerated sliding, decelerated sliding, and stabilizing. The velocity field and displacment field of the slide body is closely related to its spatial distribution. The velocity and displacement of the surface part higher than that of the shallow part. The internal friction angle and friction coefficient significantly affected the kinematic characteristics of landslide. The decrease in the internal friction angle and friction coefficient reduced the energy consumed by the friction between particles and between the particles and the sliding bed, raising the landslide velocity and displacement.